Building bridges: How to cope with the gap between today and tomorrow - Eckhard Minx (European Regional Science Association (ERSA), 1998)
The future results from what we do today, but also what we leave undone , no matter for what reasons. Many of our decisions ? especially those which concern the more distant future ? have far reaching consequences. These decisions must now, and in the future, be made in a turbulent environment both conciously and with regard to the consequences that our decisions and actions may have. Concerning European spatial perspectives, it is clear that progressing integration processes will lead to changed space-time structures. In this respect, inter-municipal and inter-regional competition for investment and employment are factors of central significance. While we will never have clear knowledge of the future, preventative thought is a prerequisite for preventative action. To recognize development early and then to assess and judge each chance and risk, is one of the best means of achieving success in the area of regional competition. Future orientation in organizations, as in planning processes, should be understood first as a process of structured communication. The basis of this is to take into consideration a large range of possible futures. Scenarios serve to prepare decisions; they don't replace decisions. Rather they make especially clear, what is sometimes forgotten or dispelled and what will remain unchanged no matter what facts arise: It befits to us to make decisions with reference to our normative goals - particularly when we cannot be completely sure of possible outcomes. We need more than ever a discussion on useful long-term models and effects of our actions, equally for towns and regions within Europe in the process of unification. This is also a form of bridge building, beyond steel and concrete, with at least the same consequences for integration as the icons of technical engineering, which, by bridging separations, enable understanding and change.
Keywords: 330